2012
DOI: 10.1007/s12105-012-0339-6
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Seromucinous Hamartoma: A Review of the Literature and a Case Report with Focal Myoepithelial Cells

Abstract: Seromucinous hamartoma is a benign lesion of the sinonasal tract. Since its description in 1974, only a small number of additional cases have been reported. It is composed of a proliferation of seromucinous glands and ducts within a variable fibrous stroma. The serous component typically stains positively for S100 (at least focally) and lacks p63 positive abluminal cells. The lack of myoepithelial/basal cells is an important diagnostic feature of seromucinous hamartoma; their absence could lead to an incorrect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“…Regarding SSH, while the ductoacinar cells are uniformly negative we did identify one case with a focal delimiting myoepithelial cell layer. Thus in keeping with a recent report that not all SSH are devoid of myoepithelial cells [32].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding SSH, while the ductoacinar cells are uniformly negative we did identify one case with a focal delimiting myoepithelial cell layer. Thus in keeping with a recent report that not all SSH are devoid of myoepithelial cells [32].…”
Section: Discussionsupporting
confidence: 92%
“…9a, b). Immunohistochemistry shows CK7, CK19 and S100 positivity with a total (or near total) absence of basal cells, confirmed by the absence of periglandular p63 staining [19] (Fig. 9c, d).…”
Section: Pathologymentioning
confidence: 68%
“…SMH was first described in 1974 as a single case report of a nasopharyngeal ''glandular (seromucinous) hamartoma'' [18]. There were scattered case reports in the intervening years, but SMH has been resurrected in earnest over the last 6 years, primarily because of its relationship to REAH and unique immunoprofile [19][20][21][22].…”
Section: Hamartomas Of the Sinonasal Tract Backgroundmentioning
confidence: 99%
“…Subsequent to that description, there have been a number of other case reports but only recently was SH the subject of larger studies, including 7 cases reported by Weinreb et al [3] and 5 cases reported by Ambrosini-Spaltro et al [4]. To date, there are less than 25 cases of SH identified in the world literature [2][3][4][5][6][7][8][9][10]. Table 2 details the comparison of various features among sinonasal hamartomas.…”
Section: Seromucinous Hamartoma (Sh)mentioning
confidence: 99%
“…In addition, calponin and muscle specific actin are negative in both the surface respiratory epithelium and the seromucinous glands. Fleming et al [8] reported a case of SH showing p63, calponin and actin staining indicating that not all SHs lack p63 reactivity. S100 protein staining is limited to the seromucinous glands.…”
Section: Immunohistochemistrymentioning
confidence: 99%